Conjugated microporous copolymer networks with enhanced gas adsorption1. Issue 17 (7th May 2015) - Yu, Miao; Wang, Xiaoyan; Yang, Xiao; Zhao, Yang; Jiang, Jia-Xing
<x xml:space="preserve">Abstract</x> Conjugated microporous copolymer networks show a high specific surface area of up to 2241 m2 g−1 and a high CO2 uptake of 4.57 mmol g−1 (1.13 bar/273 K) with a H2 uptake of 2.24 wt% (1.13 bar/77.3 K).